Evaluation of hsa-let-7d-5p, hsa-let-7g-5p and hsa-miR-15b-5p plasma levels in patients with Alzheimer's disease. (23rd December 2021) - Poursaei, Elham; Abolghasemi, Mahsa; Bornehdeli, Soghra; Shanehbandi, Dariush; Asadi, Milad; Sadeghzadeh, Mahsa; Rahmanpour, Dara; Sadeh, Reza Naghdi
Abstract : Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder MicroRNAs (miRNAs) may be promising diagnostic biomarkers for AD. Previous evidence shows that miR-15b-5p, hsa-let7g-5p and hsa-let7d-5p might confer potential blood biomarkers for timely diagnosis of AD. Therefore, in this replication study, we aimed to investigate the serum transcript level of these miRNAs to assess for their potential as diagnostic or prognostic biomarker in AD patients. Methods: Blood samples were obtained from 50 AD patients and 50 age- and sex-matched healthy individuals. Then, total RNA was extracted from serum samples, cDNA was synthesized, and the expression level of miRNAs was measured by the real-time PCR method. Results: The expression level of hsa-let7d-5p (fold change = 2.14, P = 0.007) and hsa-let7g-5p (fold change = 1.94; P = 0.013) was significantly increased in the AD patients compared to control individuals. However, the difference in the transcription of miR-15b-5p between the two groups was not statistically significant (fold change = 1.08; P = 0.76). The AROC for transcript levels of hsa-let-7d-5p was 0.68 ( P = 0.014; 95% CI, 0.39–0.88) and it was 0.64 for hsa-let-7g-5p ( P = 0.028; 95% CI, 0.27–0.89). The cut-off value for let-7d-5p had 0.82 sensitivity and 0.34 specificity. Moreover, the cut-off value for hsa-let-7g-5p indicated a 0.79 sensitivity and 0.28 specificity. Conclusion: Our findings suggest the potential of measuring the transcript levels of hsa-let7d-5p and hsa-let7g-5p miRNAs as a diagnostic biomarker for AD.